Association between compliance and personality characteristics in adolescent boys with primary arterial hypertension - Khaitovych, Mykola; Misiura, Olexiy (Psychosomatic Medicine and General Practice, 2017)
Introduction. Psychological factors influence the morbidity and mortality from cardiovascular diseases to the same extent as demographic and clinical factors, and the effectiveness of treatment is significantly associated with the patients' adherence. Male gender is associated with poor blood pressure control. Aim. To identify the personality characteristics that determine compliance in adolescent boys with primary arterial hypertension. Materials and methods. 30 boys between 13 and 17 years old (average age 14.6 ± 1.1 years) with primary arterial hypertension were examined. The compliance was evaluated using Girerd Questionnaire, type D (distress type) personality - using the DS-14 test, personality features - using the Cattell's 16 Personality Factors Test (16PF). Statistical processing of the study results was conducted using dispersion, correlation and factor analysis (main components method) with the help of “Statistica” software for Windows 8.0. Results. In 3.7% of adolescents, high compliance was noted, in 37.0% - moderate level, and in 59.3% - low. The type D personality was found in 20.0% of the examined boys. Patients with type D personality had a significantly lower (p<0.05) compliance (4.67 ± 0.63 versus 2.55 ± 0.36 points). There was found a significant direct correlation between the degree of compliance reduction and the scores on “social oppression” according to the DS-14 test (r = 0.43; p<0.01) and inverse correlation - with the value of factor N (straightforwardness-diplomacy) of the 16PF (r = -0.43; p<0.05). There were found 3 main factors that explain almost 50% of the relationships of personality characteristics of boys with primary arterial hypertension. Factor 1 (distressing ability) was related to the degree of compliance reduction (0.60), scales “negative excitability” (0.52) and “social oppression” (0.66) of the DS-14 test. This factor was also correlated with such personality features as anxiety (0.70), independence (0.65), radicalism (0.61), hardness (0.75). Factor 2 (anxiety) was most closely associated with negative excitability (0.56), intenseness (0.81), developed reasoning (0.74), low self-esteem (0.56), tenderness (0.53), suspicion (0.51) and unsociability (0.56). Factor 3 (emotional stability) demonstrated a high factor load with emotional stability (0.80), consciousness (0.69), high self-control (0.77), practicality (0.65), self-confidence (0.50). Conclusion. In adolescent boys, the reduction of compliance was mainly associated with a distressing type of personality, ignoring the social contacts, radicalism, which must be taken into account when developing a program of medical and psychological support for such patients.